Acoustic and relaxation behaviors of polydimethylsiloxane studied by using brillouin and dielectric spectroscopies - Lee, Byoung Wan; Ko, Jae-Hyeon; Park, Jaehoon; Shin, Dong-Myeong; Hwang, Yoon-Hwae (Journal of the Korean Physical Society, 2016)
The temperature dependences of the acoustic properties and the dielectric relaxation times of polydimethylsiloxane were investigated by using high-resolution Brillouin and broadband dielectric spectroscopies. The longitudinal sound velocity showed a large increase upon approaching the glass transition temperature while the acoustic absorption coefficient exhibited a maximum at ~263 K. Comparison of these results with previous ultrasonic data revealed a substantial frequency dispersion of the acoustic properties of this silicone-based elastomer. The relaxation times derived from the acoustic absorption peaks were consistent with the temperature dependence of the dielectric relaxation time of the structural a process, indicating a strong coupling between the acoustic waves and the segmental motions of the main chains.